HISTORY OF THE CONSULATE GENERAL OF THE REPUBLIC OF ARMENIA IN ODESSA (1918-1920) - DAVTYAN, D. A. (Вісник Черкаського університету. Серія: Історичні науки, 2017)
Introduction. The history of the Armenian diplomatic missions in Ukraine, as well as the history of the formation and establishment of bilateral relations, the two post-imperial countries, unfortunately, over the years did not cause interest on the part of researchers. The article describes the prerequisites for the formation of the Consulate General of the Republic of Armenia in Odessa, the operation periods, and the status of the main activities. Purpose. To analyze and study the history and stages of the diplomatic mission of the Republic of Armenia in Odessa. Given that today's Armenian studies as historiography in general, this problem has not found adequate coverage, the study of history diplomatic mission is quite important and will play back the history of this period. Results. Actually historians question consists of several works, small notes and references to published works in various synthesis. The first and only attempt to date comprehensive coverage of the history of the Armenian-Ukrainian diplomatic relations is the study of G. Petrosian Conclusion. Consulate General of the Republic of Armenia in 1918. Diplomatic representation took an active part in the issue of assistance and evacuation of Armenian refugees to Armenia. The Consulate General was closed after the establishment of Soviet power in Odessa in 1920.